Achieving development goals for HIV, tuberculosis and malaria in sub-Saharan Africa through integrated antenatal care: barriers and challenges. Issue 1 (December 2016) - Fowkes, Freya; Draper, Bridget; Hellard, Margaret; Stoové, Mark
Abstract Background The global health community is currently transitioning from the Millennium Development Goals (MDGs) to the Sustainable Development Goals (SDGs). Unfortunately, progress towards maternal, newborn and infant health MDGs has lagged significantly behind other key health goals, demanding a renewed global effort in this key health area. The World Health Organization and other institutions heralded integrated antenatal care (ANC) as the best way to address the inter-related health issues of HIV, tuberculosis (TB) and malaria in the high risk groups of pregnant women and infants; integrated ANC services also offer a mechanism to address slow progress towards improved maternal health. Discussion There is remarkably limited evidence on best practice approaches of program implementation, acceptability and effectiveness for integrated ANC models targeting multiple diseases. Here, we discuss current integrated ANC global guidelines and the limited literature describing integrated ANC implementation and evidence for their role in addressing HIV, malaria and TB during pregnancy in sub-Saharan Africa. We highlight the paucity of data on the effectiveness of integrated ANC models and identify significant structural barriers in the health system (funding, infrastructure, distribution, human resources), the adoption system (limited buy-in from implementers, leadership, governance) and, in the broader context, patient-centred barriers (fear, stigma, personal burdens) and barriers in funding structures. We highlight recommendations for action and discuss avenues for the global health community to develop systems to integrate multiple disease programs into ANC models of care that better address these three priority infectious diseases. Summary With the current transition to the SDGs and concerns regarding the failure to meet maternal health MDGs, the global health community, researchers, implementers and funding bodies must work together to ensure the establishment of quality operational and implementation research to inform integrated ANC models. It is imperative that the global health community engages in a timely discussion about such implementation innovations and instigates appropriate actions to ensure advances in maternal health are sufficient to meet applicable SDGs.